AS3MT Gene Variant Shows Association with Skin Lesions in an Arsenic Exposed Population of India: AS3MT Gene Variant Shows Association with Skin Lesions in an Arsenic Exposed Population of India - Ghosh, Soma; Chakraborty, Arijit; Das, Neelotpal; Bhowmick, Subhamoy; Majumdar, Kunal Kanti; Bhattacharjee, Samsiddhi; Mukherjee, Mouli; Sikdar, Nilabja; Pramanik, Sreemanta (Biological trace element research, 2025)
AS3MT , GSTO2 , and GSTP1 genes play important roles in the arsenic biotransformation pathway, while CYP2E1 gene has a prominent role in the metabolic activation of xenobiotics. Hence, polymorphisms of these genes might have an effect on arsenic biotransformation and could impact susceptibility to arsenical skin lesions in individuals of chronic arsenic toxicity. The present case–control study, comprising 148 subjects, attempted to evaluate genetic association between nine polymorphisms of AS3MT , GSTO2 , GSTP1 and CYP2E1 genes and arsenical skin lesions in a West Bengal (WB) population. A statistically significant association was found between rs11191439 ( AS3MT ) and arsenical skin lesions (OR = 5.50, P -value = 0.01) using logistic regression with age and gender as covariates. Among non-genetic risk factors, age and groundwater arsenic were found to be significantly associated with skin lesions ( P -value < 0.05). When haplotypes among the intragenic polymorphisms of AS3MT , CYP2E1 and GSTO2 genes were analyzed, ‘ATA’ and ‘ACG’ haplotypes of the AS3MT gene showed significant difference between the case and control. Multifactor dimensionality reduction (MDR) analysis was performed on the nine polymorphisms and groundwater and urinary arsenic for studying gene-environment interactions. Strong association was observed between groundwater arsenic and skin lesions relative to the SNPs ( P -value < 10 −5 ). The best model with maximum testing accuracy included one SNP from the AS3MT (rs11191439) and groundwater arsenic ( P -value < 0.0001). The present study documents the first report about the association of AS3MT gene variant with skin lesions in an arsenic exposed population of WB. Presumably, this is also the first study that has used MDR to investigate gene-environment interactions in arsenic-induced toxicity.